Inhibiting focal adhesion kinase (FAK) blocks IL‐4 induced VCAM‐1 expression and eosinophil recruitment in vitro and in vivo. Issue 1 (6th April 2018) - Aulakh, Gurpreet K.; Petri, Björn; Wojcik, Katarzyna M.; Colarusso, Pina; Lee, James J.; Patel, Kamala D.
Abstract: Leukocyte recruitment plays a critical role during both normal inflammation and chronic inflammatory diseases, and ongoing studies endeavor to better understand the complexities of this process. Focal adhesion kinase (FAK) is well known for its role in cancer, yet it also has been shown to regulate aspects of neutrophil and B16 melanoma cell recruitment by rapidly influencing endothelial cell focal adhesion dynamics and junctional opening. Recently, we found that FAK related non‐kinase (FRNK), a protein that is often used as a FAK dominant negative, blocked eosinophil transmigration by preventing the transcription of vascular cell adhesion molecule‐1 (VCAM‐1) and eotaxin‐3 (CCL26). Surprisingly, the blocking occurred even in the absence of endogenous FAK. To better understand the role of FAK in leukocyte recruitment, we used a FAK‐specific inhibitor (PF‐573228) and determined the effect on IL‐4 induced eosinophil recruitment in vitro and in vivo. PF‐573228 prevented the expression of VCAM‐1 and CCL26 expression in IL‐4‐stimulated human endothelial cells in vitro. As a result, eosinophil adhesion and transmigration were blocked. PF‐572338 also prevented IL‐4‐induced VCAM‐1 expression in vivo. Using brightfield intravital microscopy, we found that PF‐573228 decreased leukocyte rolling flux, adhesion, and emigration. We specifically examined eosinophil recruitment in vivo by using an eosinophil‐GFP reporter mouse and found PF‐573228 attenuated eosinophil emigration. This study reveals that a FAK inhibitor influences inflammation through its action on eosinophil recruitment. Abstract : FAK inhibitor affects eosinophil recruitment in vivo using a new eosinophil reporter animal.